EXAMINING THE EVOLUTION OF THE ROMANIAN SYSTEM OF ACCOUNTS - TEIUȘAN, Sorin Ciprian (Annales Universitatis Apulensis Series Oeconomica, 2014)
Audits carried out in accordance with International Standards on Auditing or International Standards on Review Engagements and procedures undertaken by the independent auditor made under the International Standard on Related Services are two totally different commitments in terms of the independent auditor to express an audit opinion on a report. What happens when on these types of commitment a comparative analysis is performed to highlight the strengths and weaknesses of each, and not least the need to inform the beneficiaries meeting report issued by the independent auditor. The empirical study presented aims to present, the context of an atypical commitment, a solution of the type of mission which may be subject to a commitment by the auditor, studying comparatively the relevant standards applicable or audit missions as appropriate, based on ISA 700 Formulating an opinion and reporting on financial statements, ISA 800 Special considerations - Audits of financial statements prepared in accordance with special purpose frameworks, ISA 600 Special considerations - Audits of group financial statements (including the work of component auditors), ISRS 4400 Engagements to perform agreed-upon procedures regarding financial information and ISRE 2400 Engagements to Review Historical Financial Statements and highlighting of relevant information to users.